Guido Aristarco: From Lascia o Raddoppia? to Broadcast Media - Matteo Macaluso (Cinergie, 2023)
This paper analyzes various documents from the archive at the library of the Cineteca di Bologna, "Renzo Renzi", which corroborate a professional collaboration between film critic Guido Aristarco and the state-run broadcaster Radiotelevisione Italiana (Rai) for the popular TV show Lascia o raddoppia? in 1956. These materials, including lists of questions about history of cinema, are a resource for recent studies that regard Italian film criticism as a relational system. More precisely, it is yet another in step in the historicization of a high-profile figure like Guido Aristarco and investigates the ways in which Aristarco used broadcast media, which occupied a central position in the media system during this period, as a pace for action within the complex dynamics of modern mass society.